Navigating Corporate Responsibility: How Auto Industry Executives Align CSR Challenges with Sustainable Development Goals (Journal of Informatics Education and Research, 2024)
Purpose: This study aims to explore the perceptions of corporate social responsibility (CSR) aligned with SDGs held by executives in the automobile sector, using Carroll's CSR model as the theoretical framework. Additionally, the study investigates the influence of demographic factors, such as gender, age, position, and work experience, on CSR perception.Methodology: The study employs a quantitative research approach, with data collected through a survey administered to 244 executives in the automobile industry. Statistical analyses, including validity and reliability assessments, path coefficients, and construct measurements, are conducted using Smart PLS software to examine the relationships between variables.Findings: The findings reveal that executives in the automobile sector place greater emphasis on economic and social issues compared to philanthropic and legal aspects of CSR driven by concerns about profitability and shareholder value. The study identifies key factors shaping CSR perception, including executive priorities, project design challenges, top management commitment, and beneficiary responses. Notably, gender significantly impacts CSR perception, underscoring the importance of diversity and inclusiveness in CSR management.Top of FormNovelty: This research contributes novelty by comprehensively exploring how CSR challenges specifically align with Sustainable Development Goals (SDGs) in the automobile industry. It not only unpacks the nuances of executive perspectives on this alignment but also offers a novel approach for assessing the interaction between demographic factors and CSR challenges as they relate to SDGs.Implications: The study emphasizes the necessity for businesses to address economic challenges, engage with policymakers, and adopt sustainable practices to align managers' interests with social objectives. It also emphasizes the importance of collaboration with stakeholders, including academia, government, and NGOs, to bridge gaps in understanding the philanthropic and legal aspects of CSR. Companies can use these insights to enhance their CSR strategies, contribute to sustainable development, and cultivate a corporate culture that values and promotes sustainability.